2021
DOI: 10.7717/peerj.11562
|View full text |Cite
|
Sign up to set email alerts
|

Marathon race performance increases the amount of particulate matter deposited in the respiratory system of runners: an incentive for “clean air marathon runs

Abstract: Background In the last decades, marathon running has become a popular form of physical activity among people around the world. It should be noticed that the main marathon races are performed in large cities, where air quality varies considerably. It is well established that breathing polluted air results in a number of harmful effects to the human body. However, there have been no studies to show the impact of marathon run performance on the amount of the deposition of varied fractions of airbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The best records of the marathon runs were achieved in spring or autumn, early in the morning and with an external temperature between 10 and 15°C ( 25 ). Recently it has been shown as airborne particulate matter (PM 10 ) can settle in the airways of runners ( 26 ). The main marathons take place in large, generally highly polluted cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best records of the marathon runs were achieved in spring or autumn, early in the morning and with an external temperature between 10 and 15°C ( 25 ). Recently it has been shown as airborne particulate matter (PM 10 ) can settle in the airways of runners ( 26 ). The main marathons take place in large, generally highly polluted cities.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution can reduce the marathon performance, at least in women (every 10 μg m −3 in PM 10 , performance decrease by 1.4%) ( 27 ), as well as having a negative impact on health. To ensure “clean air” for elite runners, the PM content should be <5.5 μg m −3 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zoladz et al. found that PM 10 deposition in marathon runners was 6–10 times higher than those at rest [ 22 ]. Therefore, the public is more likely to be exposed to air pollution during outdoor physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…; [ 14 ]). This is explained by the greater fraction of air inhaled during exercise, effectively bypassing the normal nasal filtration mechanisms in the case of particles, and the increased airflow velocity, carrying pollutants deeper into the respiratory tract [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%